Physicochemical properties and biochemical profiling of local commercial Forest and Tualang honeys - Haslina Asis; Ahda S. Riadi; Muhamad Arifin; Ismail Ware; Cahyo Budiman (Faculty of Pharmacy, University of Benin, 2024)
Local varieties of honey from Sabah, such as Forest honey (FH) and Tualang honey (TH), are renowned for their manifold health benefits and diverse compounds, which are influenced by floral sources and geographical locations. Despite their prevalence, the physicochemicals, microbial properties, and metabolite compounds of these honey variants remain unexplored. The study aims to analyze and present the physicochemical and biochemical compositions of two local honeys purchased from the local market in Kundasang, Sabah, Malaysia. Both honey samples exhibited comparable characteristics in terms of moisture, fat, sugar content, and pH values, falling within the standard range for honey. However, FH demonstrated higher ash and protein levels than TH, with FH's ash and protein contents at 0.23±0.04% and 0.72±0.01%, respectively, contrasting with TH's 0.11±0.01% and 0.34±0.01%. Hydroxymethylfurfural (HMF) levels differed significantly between the two samples, registering 1.78±0.12% for FH and 2.86±0.04% for TH, both of which are within acceptable consumption ranges. Total plate count findings indicated a significant difference, with 1.02±0.03 log CFU/g for FH and 0.41±0.002 log CFU/g for TH, yet within recommended safe limits. Liquid Chromatography-Quadrupole Time of FlightTandem Mass Spectrometry (LC-QTOF-MS) revealed TH yielded 20 compounds, surpassing FH's 16 compounds, including previously unreported compounds. Given the diverse compounds' versatility,